Ukraine’s Green Economy Growth in the Context of Industry 4.0: Challenges and Solutions - Korohodova, Olena; Moiseienko, Tetiana; Hlushchenko, Yaroslava; Chernenko, Natalya (Ekonomika, 2024)
The research highlights the importance of prioritizing new sources of economic growth for the world, with a specific focus on Ukraine. The information base of the study included data from the statistical and managerial reporting of enterprises, the State Statistics Service of Ukraine, and information-analytical materials from international organizations. The authors analyze scientific works associated with the European Green Deal (EGD) to identify historic periods of green economy growth and establish growth trends. The authors argue that favorable conditions are necessary to achieve sustainable green growth within the framework of the EGD. The study aims to introduce an improved economic definition, namely the efficiency of green (natural) capital, aligned with the provisions of the EGD in the context of Industry 4.0. The analysis demonstrated that the coefficient of green (natural) capital (GNC) efficiency is crucial in decision-making processes by enterprises, taking into account ecological and green (natural and resource) factors. The analysis also includes a flowchart of Ukraine‘s green economy growth in the environment of Industry 4.0 as of 2022. The research results have led to the improvement of scientific and methodological approaches to assessing the eco-economic efficiency of advanced green technologies. The introduced green (natural) capital indicator allowed to display of the theory of achieving more products and services with fewer resources, including natural and ecological ones.
Keywords: Green Growth Indicators; European Green Deal; efficiency of green (natural) capital; Industry 4.0